Evaluation of adaptation of ceramic inlays using optical coherence tomography and replica technique - TURK Ayse Gozde; SABUNCU Metin; ULUSOY Mubin (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Optical coherence tomography (OCT) has generally been used as a nondestructive technique to evaluate integrities of composite restorations. We investigated marginal and internal adaptations of ceramic inlay restorations with OCT and compared them to results with the silicone replica technique. Round-shaped class I cavities were prepared on 16 human maxillary first premolar teeth. Ceramic inlays were fabricated. Silicone replicas from inlays were obtained and sectioned to measure marginal and internal adaptations with a stereomicroscope (Leica Dfc 295, Bensheim, Germany). Inlays were cemented on respective teeth. Marginal and internal adaptations were then measured with the OCT system (Thorlabs, New Jersey, USA) in 200- μm intervals. Replica and OCT measurements were compared with independent samples t-tests. A paired t-test was used to evaluate the marginal and internal adaptations of each group (p < 0.05). Marginal and internal adaptations were 100.97 ± 31.36 and 113.94 ± 39.75 μm, respectively, using the replica technique and 28.97 ± 17.86 and 97.87 ± 21.83 μm, respectively, using OCT. The differences between the techniques were significant (p = 0.00 and p = 0.01, respectively). On evaluation within the groups, internal adaptation values were found to be significantly higher than the marginal adaptation values for the replica technique (p = 0.00) and OCT (p = 0.00). Therefore, the replica and OCT techniques showed different results, with higher values of marginal and internal adaptation found with the replica technique. Marginal and internal adaptation values of ceramic inlays, whether measured by replica or OCT techniques, were within clinically acceptable limits.